(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Linguistics is the pivot of literature determining its importance in the contemporary society. The merit of a literary text largely depends on the language as it reflects the politics evaluated by the author in an impressive way. In the research paper entitled “Postcolonial Socio-Cultural Linguistics in Aravind Adiga’s The White Tiger” explores the matter and manner in the linguistic narration. The discourse travels from postcolonial hybridity and marginality to postmodern co-existence. Various literary tools used by Adiga and the liberty taken by him to discuss the drastic change over in the attitude of the contemporary socio-cultural scenario are evaluated. The author has attempted to subvert the elitist historiography and to create a common platform for the co-existence of the elite and subaltern narratives. He has made use of the postcolonial discourse to erase the bordering perceptions and paved way for mutual coexistence where both the centre and periphery can overlap and take the other side with strenuous effort.